Analysis of Adoption Gaps and their Causes in Major Crops Grown in Basti District of Uttar Pradesh (Indian Journal of Extension Education, 2013)
The present study was carried out in Basti district of Uttar Pradesh to know the adoption gap and their causes. It was observed that maximum gaps were found in seed treatment, application of micronutrients, plant protection measure and inter cultural practices in the major crops i.e. wheat, rice, sugarcane, potato and mustard, except inter culture practices in potato crop. There were no gaps in sowing time, varieties, seed rate, application of FYM, water management, crop harvesting and post harvest technology. Whereas, maximum partial gap was found in methods of fertilizer application. The major causes were unawareness about the technology, lack of skills, poor resources, non- conviction about the technology, unavailability of inputs at proper time and risk orientation.